Paradoxical whole genome DNA methylation dynamics of 5'aza-deoxycytidine in chronic low-dose exposure in mice. Issue 2 (1st February 2021) - Colwell, Mathia; Wanner, Nicole M.; Drown, Chelsea; Drown, Melissa; Dolinoy, Dana C.; Faulk, Christopher
ABSTRACT: Decitabine (5-aza-2ʹdeoxycytidine; DAC) is a DNA methyltransferase inhibitor used to hypomethylate the epigenome. Current dosing regimens of DAC for use in mice vary widely and their hypomethylating ability has not been robustly characterized, despite reliable results of hypomethylation of the epigenome with cell lines in vitro and tissue specificity in vivo . We investigated the effects on the DNA methylome and gene expression within mice exposed to chronic low doses of DAC ranging from 0 to 0.35 mg/kg over a period of 7 weeks without causing toxicity. Our dose paradigm resulted in no cytotoxic effects within target tissues, although testes weight and sperm concentration significantly reduced as dose increased (p-value <0.05). By whole genome bisulphite sequencing (WGBS), we identify tissue and dose-specific differentially methylated CpGs (DMCs) and regions (DMRs) in testes and liver. Testes methylation is more sensitive to DAC exposure when compared to liver, cortex, and hippocampus. Gene expression was dysregulated in testes and liver, targeting non-specific pathways as dose increases. Together our data suggest DNA methylation and gene expression are disrupted by in vivo DAC treatment in a non-uniform manner contrary to expectations, and that no dose level or regimen is sufficient to cause systemic hypomethylation in whole mice.